(untitled) (AYUSHDHARA, 2017)
The knowledge of ‘Ayurveda’ (The science of life) came from Lord ‘Brahma’ before the creation of the Universe. The original form of Ayurveda was incorporated in ‘Astanga Ayurveda’ or Eight branches of Ayurveda i.e Kaya (Internal medicine), Bala (Paediatrics), Graha (Demonology /Psychiatry), Urdhanga (Diseases of Eye’s, Ear’s, Nose, Throat and Head), Salya (Surgery), Damstra (Toxicology), Jara (Geriatrics), Vrisha (Virilification therapy), The ‘Astanga Samgraha’ was written by Vagbhata, which gives clear evidence regarding existence of ‘Astanga Ayurveda’.‘Damstra’/‘ Visa Vairodhikam’/ ‘Agadatantra’ (Toxicology) is also an important branch among them which deals with the diseases and treatment due to poison. Comparing to modern Toxicology, In Ayurveda, it has been mentioned vividly with the concept of various Antidotes and their use in the treatment of different types of poisoning. In ‘Astanga Samgraha’ the knowledge or concept regarding ‘Damstra’/’Agada Tantra’ is mentioned scattered and unsequentially throughout the text. So that, it will be hard for someone to find the matters according to his needs. If we look into the present era, it is an era of super specialization and advanced techniques. So, it is very necessary that ‘Ayurveda’ also be updated keeping similarity with the changing time and need of the people. In my present work, I have collected all the concepts of ‘Damstra’/‘Agadatantra’ (Toxicology) from all parts of ‘Astangasamgraha’ and arranged the matters in the form of Hetu (Causes), Linga (Symptoms), Ausadha (Treatments) of different types of poisoning mentioned in ‘Astanga Samgraha’ and also tried to calculate the percentage of ‘Agadatantra’ /‘Damstra’ mentioned in this text.